Demography Oreomunnea mexicana (Standl.) J. F. Leroy in the cloud forest of Sierra Juárez, Oaxaca - Pacheco-Cruz, Nelly; Clark-Tapia, Ricardo; Campos-Contreras, Jorge E.; Gorgonio-Ramírez, Montserrat; Luna-Krauletz, Maria Delfina; Naranjo-Luna, Francisco José; Alfonso Corrado, Cecilia Liana (Instituto de Ecología, A.C., 2018)
The demography of Oreomunea mexicana, an endangered species was studied. This species is a Cenozoic relic and is a dominant tree in the cloud mountain forest of Sierra Juárez, Oaxaca. Population structure of four populations were obtained through plots of 400 m2 (20 x 20 m) for the years 2011 and 2016. Through the use of Lefkovitch-type matrices, the finite population growth rate (λ) and an elasticity analysis were obtained for the population of San Bernardo over two time periods (2011 - 2015 and 2015 - 2016). Strong winds of 100 km/hr were recorded on March 2016, that increased the mortality within the studied populations, without modifying its population structure in an inverted J-shape. However, the demographic study in San Bernardo showed a λ in decrease for the second period of 0.44 ± 0.009, in compared to a growth of λ (1,101 ± 1.083) found in the first period. The permanence of individuals is the most important demographic parameter in maintaining viability demographic in O. mexicana. The species presented a high sensitivity and vulnerability to extreme environmental changes, with a decrease in population number in a short period of time (2015-2016). Therefore, if it is desired to restore these local populations, is absolutely essential that conservation efforts focus on maintaining and increasing the number of adult individuals in the area in the future.